Impact of neoadjuvant chemotherapy on survival and recurrence patterns after robot‐assisted radical cystectomy for muscle‐invasive bladder cancer: Results from the International Robotic Cystectomy Consortium. (19th December 2021) - Gopalakrishnan, Dharmesh; Elsayed, Ahmed S; Hussein, Ahmed A; Jing, Zhe; Li, Qiang; Wagner, Andrew A; Aboumohamed, Ahmed; Roupret, Morgan; Balbay, Derya; Wijburg, Carl; Stockle, Michael; Dasgupta, Prokar; et al.
Abstract : Objectives: To analyze the impact of neoadjuvant chemotherapy on survival and recurrence patterns in muscle‐invasive bladder cancer after robot‐assisted radical cystectomy. Materials and methods: The International Robotic Cystectomy Consortium database was reviewed to identify patients who underwent robot‐assisted radical cystectomy for muscle‐invasive bladder cancer between 2002 and 2019. Survival outcomes, response rates, and recurrence patterns were compared between patients who received neoadjuvant chemotherapy and those who did not. Survival distributions were estimated using Kaplan–Meier analyses and compared using the log‐rank test. Results: A total of 1370 patients with muscle‐invasive bladder cancer were identified, of whom 353 (26%) received neoadjuvant chemotherapy. After a median follow‐up of 27 months, neoadjuvant chemotherapy recipients had higher 3‐year overall survival (74% vs 57%; log‐rank P < 0.01), 3‐year cancer‐specific survival (83% vs 73%; log‐rank P = 0.03), and 3‐year relapse‐free survival (64% vs 48%; log‐rank P < 0.01). Neoadjuvant chemotherapy was a predictor of higher overall survival, cancer‐specific survival, and relapse‐free survival in univariate but not multivariate analysis. Pathological downstaging (46% vs 23%; P < 0.01), complete responses (24% vs 8%; P < 0.01), and margin negativity (95% vs 91%; P < 0.01) at robot‐assisted radical cystectomy were more common in the neoadjuvant chemotherapy group. Neoadjuvant chemotherapy recipients had lower distant (15% vs 22%; P < 0.01) but similar locoregional (12% vs 13%; P = 0.93) recurrence rates. Conclusions: In this analysis from a large international database, patients with muscle‐invasive bladder cancer who received neoadjuvant chemotherapy before robot‐assisted radical cystectomy had higher rates of survival, pathological downstaging, and margin‐negative resections. They also experienced fewer distant recurrences.